Inhibition Effects of Some Phenolic Anthraquinone Derivatives on Lactoperoxidase Activity: A Detailed in Vitro and in Silico investigation - Korkmaz, Isil Nihan; Senol, Halil; Kalin, Ramazan (Springer, 2025)
The basic nutrient of all living beings in the developmental age is milk. Milk contains many things necessary for ideal nutrition. One of the enzymes found in bovine milk is lactoperoxidase (LPO; EC 1.11.1.7). The LPO system functions as a natural defense system, especially in newborn babies. Despite the many benefits of milk, contamination of breast milk with environmental toxins is common. Over time, people accumulate a lifetime load of chemicals from drugs to environmental pollutants, and these can be passed on to the baby during breastfeeding. Anthraquinones are colorful compounds that can be produced both naturally and synthetically. These compounds are widely used in industry and medicine due to their biological activities and colorful structures. In this study, in vitro enzyme inhibition study, molecular docking and molecular dynamics (MD) simulation parameters were examined to investigate the inhibitory potential of anthraquinone derivatives, which are widely used as coloring agents, against the lactoperoxidase enzyme. The inhibitors showed competitive inhibition with Ki values between 0.4964 +/- 0.042-2.0907 +/- 0.1044 mu M. 1,2-Dihydroxy-anthraquinone was predicted to have the highest affinity on the LPO receptor, with estimated free binding energies of -7.11 kcal/mol. The stability of both ligand and protein, as shown by the low RMSD and RMSF values, shows that 1,2-dihydroxy-anthraquinone (2) maintains strong and stable interactions throughout the MD simulation, further supporting the high binding affinity and potential biological activity of the compound. We hope that this study will guide the development of drugs targeting the LPO enzyme with anthraquinone derivatives.
Keywords: Lactoperoxidase; Anthraquinone; Molecular docking; Molecular dynamics (MD) simulations